Antihypertension medication adherence and associated factors at Dessie Hospital, North East Ethiopia, Ethiopia - Chelkeba, Legese; Dessie, Sisay (International Journal of Research in Medical Sciences, 2017)
Hypertension is an overwhelming global challenge. Despite the development of many effective anti hypertensive drugs, target to reduce morbidity and mortality due to high blood pressures are reached in only a minor of patients in clinical practice. Poor adherence is one of the biggest obstacles in therapeutic control of blood pressures. There are complaints from patients and physicians that the poor result of actual antihypertensive drug therapies. Many people with age indifference are attacked by this “silent killer” or which results in target organ damage as a complication. The aim of this study was to assess the magnitude of adherence and the factors associated with non-adherence to anti-hypertensive medication. Cross sectional exclusively convenient study was conducted by using structured questionnaires consisting of open and closed-ended questions on patients diagnosed for hypertension and have already been on anti hypertensive medications at least for three months at Dessie Referral hospital from 20/01/2012 to 29/01/2012. A total of hundred hypertensive patients were screened from hundred six cases by the exclusive criteria and the overall incidence of anti-hypertensive medication non adherence was 26%. The study identifies reasons why patients don’t adherent with the drug regiments. Among Factors associated with non adherence were health system and health care provider poor interaction with patient and therapy factors like frustration and unwanted effect of the medication in the long run. There was indication of non adherence from the study area. Great emphasis should be placed on intervention strategies such as patient counseling and increasing awareness of the physicians, all other prescribers and health care providers at large about the non adherence of anti hypertensive drugs as well as the complication what comes due to this medication non adherence.